Physical theraphy management of patients with spinal pain an evidence-based approach - Stetts, Deborah M., 1954- (Slack Incorporated, 2014)
Physical Therapy Management of Patients with Spinal Pain: An Evidence-Based Approach is an essential reference text to stay in stride with the recent health care education trend of evidence-based practice. The use of clinical data supported by external research provides an increased likelihood of successful client treatment, ultimately leading to improved patient quality of life. Drs. Stetts and Carpenter evaluate research in spinal pain and present their findings in a format that allows for easy transition from the text to actual clinical cases. Each chapter outlines history, examination, diagnosis, management guidelines, and case studies. The combination of a text, along with video clips provides physical therapy students and clinicians with the latest evidence-based research in spinal pain and the tools to put these findings into practice. Additionally, Physical Therapy Management of Patients with Spinal Pain: An Evidence-Based Approach provides easy access to its companion website containing narrated video content.